2020
DOI: 10.2147/ott.s257052
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of TP53 Mutations with Response to Anlotinib Treatment in Advanced Non-Small Cell Lung Cancer</p>

Abstract: Multitargeted antiangiogenic drugs have demonstrated significant antitumor activity against a variety of solid tumors. Anlotinib, a novel oral multitargeted antiangiogenic tyrosine kinase inhibitor, was approved as a third-line treatment for advanced NSCLC in China. However, predictive biomarkers are currently insufficient and are urgently required. Herein, we report three pre-treated cases of advanced NSCLC with TP53 mutations, wherein these patients showed partial response to anlotinib. Moreover, the three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The therapeutic effect reached PR and PFS was more than 7 months ( 26 ). The K-RAS mutation status may be an indicator of good response to the PD-1 mAb, the TP53 mutation patients also showed good response to anlotinib ( 27 ). So clinical trial like combination of anlotinib and PD-1 mAb may be promising in patients with K-RAS mutation and TP53 mutation co-existed.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effect reached PR and PFS was more than 7 months ( 26 ). The K-RAS mutation status may be an indicator of good response to the PD-1 mAb, the TP53 mutation patients also showed good response to anlotinib ( 27 ). So clinical trial like combination of anlotinib and PD-1 mAb may be promising in patients with K-RAS mutation and TP53 mutation co-existed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antiangiogenic inhibitors have a therapeutic effect on patients with TP53 mutations [26]. A case report described the favorable response to anlotinib in three patients with advanced NSCLC harboring TP53 mutation [27]. Of course, the above further proved that the patient had a good effect because of the combination of afatinib and anlotinib.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Onco Targets and Therapy reported three advanced lung cancer patients with TP53 mutations, which responded well to anlotinib. 18 Other authors also reported the role of the Tp53 protein in inhibiting angiogenesis and angiogenesis. 19 , 20 This is consistent with some previous reports that TP53 mutations are sensitive to angiogenesis, suggesting that patients with Tp53 mutations may be a potential benefit group for anlotinib.…”
Section: Discussionmentioning
confidence: 98%